2017
DOI: 10.1042/bst20170091
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry techniques for studying the ubiquitin system

Abstract: Post-translational control of proteins through covalent attachment of ubiquitin plays important roles in all eukaryotic cell functions. The ubiquitin system in humans consists of 2 E1, 35 E2 and >600 E3 ubiquitin ligases as well as hundreds of deubiquitylases, which reverse ubiquitin attachment. Moreover, there are hundreds of proteins with ubiquitin-binding domains that bind one of the eight possible polyubiquitin chains. Dysfunction of the ubiquitin system is associated with many diseases such as cancer, aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 78 publications
0
39
0
Order By: Relevance
“…In order to identify the K63‐polyubiquitylated proteins, which bind the TAK1/MKK7/JNK complex on the phagosome of M2 macrophages, we enriched polyubiquitylated phagosomal proteins from M2 macrophages using tandem ubiquitin‐binding entities (TUBEs) of a repeat of the Npl4 Zinc Finger (NZF) domain of TAB2 tagged with Halo (termed here Halo‐TAB2). These constructs have been shown to bind specifically to K63‐polyubiquitin chains (Fig A; Hjerpe et al , ; Emmerich et al , ; Heap et al , ). Quantitative mass spectrometric analysis of these pull‐downs identified 538 phagosomal proteins that were reproducibly captured by Halo‐TAB2 compared to mutant, ubiquitin‐non‐binding Halo (T674A/F675A) TAB2 control beads (based on a twofold, P < 0.05 cut‐off; Dataset EV2).…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify the K63‐polyubiquitylated proteins, which bind the TAK1/MKK7/JNK complex on the phagosome of M2 macrophages, we enriched polyubiquitylated phagosomal proteins from M2 macrophages using tandem ubiquitin‐binding entities (TUBEs) of a repeat of the Npl4 Zinc Finger (NZF) domain of TAB2 tagged with Halo (termed here Halo‐TAB2). These constructs have been shown to bind specifically to K63‐polyubiquitin chains (Fig A; Hjerpe et al , ; Emmerich et al , ; Heap et al , ). Quantitative mass spectrometric analysis of these pull‐downs identified 538 phagosomal proteins that were reproducibly captured by Halo‐TAB2 compared to mutant, ubiquitin‐non‐binding Halo (T674A/F675A) TAB2 control beads (based on a twofold, P < 0.05 cut‐off; Dataset EV2).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm that the observed reduction in ubiquitin conjugates is related to polyubiquitin chains that are targeted to proteasomal degradation (Kulathu & Komander, ), we treated MCF7 cells with 1 μM palbociclib for 10 h in the presence or absence of the proteasome inhibitor bortezomib. We then enriched total polyubiquitin and analyzed the linkages by targeted parallel reaction monitoring (PRM) mass spectrometry (Heap et al , ). This analysis confirmed that amounts of K48 chains, as well as the K6, K29, and K63 chains, were significantly reduced upon palbociclib treatment, and this reduction was dependent on proteasomal activity (Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…However, in most cases, they are due to changes in their activities, which is more challenging to monitor, in particular in patient samples. Mass spectrometry has been widely used to analyze, at the proteome scale, cell protein SUMOylome and Ubiquitylome (Heap et al, 2017;Hendriks & Vertegaal, 2016).…”
Section: Dysregulations Of the Ubiquitin And Sumo Conjugated Proteomementioning
confidence: 99%